ANALISIS KINERJA WI-FI CHANNEL 1, 3, 6 DAN 11 DENGAN MENGGUNAKAN BANDWIDTH 20 MHz DAN 40 MHz PADA FREKUENSI WI-FI 2.4 GHz SPESIFIKASI 802.11n - Fajriati, Nur (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2020)
Abstract. This research aims to analyze the performance of Wi-Fi channels 1, 3, 6, and 11 in the bandwidth (channel width) of 20 MHz and 40 MHz in accordance with the IEEE 802.11n protocol. This research uses an experimental research method with a Pre-Experimental experimental design. Measurements made by looking at the parameters of Quality of Service is delay, throughput and packet loss by considering the results of observations of Spurious Emission. By transmitting data using Iperf3 and the Ping command (CMD). Based on the final results of the analysis it can be concluded that at bandwidth (channel width) 20 MHz, the best channels to use are channels 1, 6, and 11. As for bandwidth (channel width) 40 MHz, the best channels to use are channels 3 and 11. Spurious Emission produced is also still included as recommended by Rec. ITU-R SM.329-7 Spurious Emissions.